Implications of O-glycan modifications in the hinge region of a plant-produced SARS-CoV-2-IgA antibody on functionality - Uetz, Pia; Göritzer, Kathrin; Vergara, Emil; Melnik, Stanislav; Grünwald-Gruber, Clemens; Figl, Rudolf; Deghmane, Ala-Eddine; Groppelli, Elisabetta; Reljic, Rajko; Ma, Julian K.-C.; Stöger, Eva; Strasser, Richard (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Prolyl-4-hydroxylases (P4H) catalyse the irreversible conversion of proline to hydroxyproline, constituting a common posttranslational modification of proteins found in humans, plants, and microbes. Hydroxyproline residues can be further modified in plants to yield glycoproteins containing characteristic O-glycans. It is currently unknown how these plant endogenous modifications impact protein functionality and they cause considerable concerns for the recombinant production of therapeutic proteins in plants. In this study, we carried out host engineering to generate a therapeutic glycoprotein largely devoid of plant-endogenous O-glycans for functional characterization.Methods: Genome editing was used to inactivate two genes coding for enzymes of the P4H10 subfamily in the widely used expression host Nicotiana benthamiana. Using glycoengineering in plants and expression in human HEK293 cells we generated four variants of a potent, SARS-CoV-2 neutralizing antibody, COVA2-15 IgA1. The variants that differed in the number of modified proline residues and O-glycan compositions of their hinge region were assessed regarding their physicochemical properties and functionality.Results: We found that plant endogenous O-glycan formation was strongly reduced on IgA1 when transiently expressed in the P4H10 double mutant N. benthamiana plant line. The IgA1 glycoforms displayed differences in proteolytic stability and minor differences in receptor binding thus highlighting the importance of O-glycosylation in the hinge region of human IgA1. This is a provisional file, not the final typeset article Discussion: This work reports the successful protein O-glycan engineering of an important plant host for recombinant protein expression. While the complete removal of endogenous hydroxyproline residues from the hinge region of plant-produced IgA1 is yet to be achieved, our engineered line is suitable for structure-function studies of O-glycosylated recombinant glycoproteins produced in plants.